Augmented and quenched local moments in a van der Waals itinerant moiré ferromagnet - Mohanty, Saransha (2023)
Twisted two-dimensional (2D) van der Waals (vdW) quantum materials are renowned for their uncanny features like unconventional superconductivity, metal insulator transition (Mott transition), spin liquid phase etc., offering a rich landscape for strong electron correlations. Such electronic correlations also account for unusual magnetism in twisted crystals. However, advancement in the field of 2D twisted magnetism has been constrained, owing to lack of ideal materials as well as proper ways to design moiré magnets correlating their emergent magnetic and electronic properties. Here, we design a vdW moiré magnet and demonstrate that the simple act of rotating two monolayers i.e., 1T-NbSe2 and 1T-VSe2 at various twist angles, produces an inhomogeneous mixture of augmented and quenched localized magnetic moments per transition metal vanadium (V) and niobium (Nb) atoms. Precisely, twist angle affects the induced local magnetic moments of each constituent layers. Notable flat bands and itinerant ferromagnetism emerge in vdW moiré superlattice, the latter satisfying Stoner criterion. These features result from orbital rehybridization at atomic lattice sites instead of interlayer coupling between layers. Moreover, orbital magnetism is identified in untwisted heterobilayer system. The results present an effective strategy for designing moiré magnets with insights into new quantum-mechanical phenomenon of twist regulated on-site magnetism.